FORMULATION AND CYTOTOXICITY EVALUATION NANOEMULSION OF JERUJU LEAVES (ACANTHUS ILLICIFOLIUS L) ETHANOL EXTRACT ON T47D BREAST CANCER CELLS - RAHAYU, HENI SETYOWATI ESTI; DIANITA, PUSPITA SEPTIE; WIJAYANTI, KARTIKA; HARESMITA, PERDANA PRIYA (International Journal of Applied Pharmaceutics, 2025)
Objective: The first cause of death in the world is cancer. The type of cancer that is often found in women is breast cancer. Various treatments and therapies have been carried out, but the incidence of cancer is increasing. This is caused by lifestyle, nutrition and environmental conditions. Cancer drugs are very toxic, expensive and resistant, so it is necessary to try other therapies that are safe, do not damage other body cells, and do not cause side effects, namely herbal or plant-based therapies. One plant that has potential as a breast cancer therapy is jeruju (Acanthus Illicifolius L) leaves. The aim of this research was to determine the cytotoxic effect of jeruju leaf extract (Acanthus Illicifolius L) on T47D breast cancer cells in a nanoemulsion preparation. Methods: Extraction of jeruju leaves was carried out using 96% ethanol solvent, then cytotoxicity testing was carried out using the MTT test on T47D cell proliferation, then the IC50 value was calculated using a linear regression equation and continued with the preparation and testing of nanoemulsion preparations. Results: Jeruju leaf extract (Acanthus Illicifolius L) has a strong cytotoxic activity value measured by an IC50 value of 1.357 µg/ml and can be packaged in a nanoemulsion preparation which has a particle size of 16.1 nm. These findings indicate that jeruju leaf extract is effective in inhibiting T47D cells in vitro. Conclusion: Jeruju leaf extract (Acanthus Illicifolius L) has a strong cytotoxic activity value measured by an IC50 value of 1.357 µg/ml and can be packaged in a nanoemulsion preparation which has a particle size of 16.1 nm.